Maneckiite, ideally NaCa2Fe22+(Fe3+Mg)Mn2(PO4)6(H2O)2, a new phosphate mineral of the wicksite supergroup from the Michałkowa pegmatite, Góry Sowie Block, southwestern Poland. (1st May 2017) - Pieczka, Adam; Hawthorne, Frank; Gołe¸biowska, Bożena; Włodek, Adam; Grochowina, Anna
Maneckiite, ideally NaCa